Strengthen the character building of the Indo Malay people and literary works - --, Risnawaty (2013)
This paper is addressing the cultural competition of globalizing world by putting the national character materials of the Indo-Malay to all courses in the university level.The designed core courses in which the cultural contains reemphasized takes our attention in facing currently global phenomena.For instance literature works have an important role in the formation of the character building either in schools or in society.Avoiding of the local values lost is very necessary and the university should change and stress the national character.It becomes a crucial issue in Indo-Malay Archipelago to explore the vital role of literary works.It needs to prioritize in designing contents of core course in Indonesia and Malaysia.In reality, we see one to be rough, corruptive, nepotism, and loose the humanism that could lead to the national disintegration.To overcome this problem, we have to maintain the literature and culture course.It suggests educators to have students reading the literary books that contain local values.